Safety and tolerability of topical trametinib in rosacea: Results from a phase I clinical trial - Edward J. Wladis; Jacqueline Busingye; Leahruth K. Saavedra; Amy Murdico; Alejandro P. Adam (Skin Health and Disease, 2024)
Abstract Purpose Overactivation of the mitogen activated kinase pathway has been associated with rosacea. We hypothesised that inhibitors of this pathway can be repurposed to alleviate rosacea symptoms. Methods In order to test this hypothesis, we designed a double‐blind, randomised, placebo‐controlled phase I clinical trial to assess the safety and tolerability of a first‐in‐kind topical formulation of a MEK kinase inhibitor, trametinib. Subjects applied daily trametinib‐containing cream (0.05 mg in 0.5 mL) to one cheek and cream without inhibitor to the other for consecutive 21 days. Skin irritation scores and blood samples were obtained during visits on days 8, 15 and 22. Results On analysis of high‐performance liquid chromatography, no systemic trametinib absorption was detected during this treatment period. Subjects demonstrated a slight but significant improvement in both cheeks, regardless of drug contents. No adverse effects were reported during this time. Conclusions Topical trametinib was well tolerated at a dose of 0.05 mg per day without meaningful systemic absorption or local adverse events. A dose escalation trial is warranted to determine optimal dosing to treat rosacea while avoiding the adverse effects of systemic treatment.